How has been the impact on the ICANH budget in implementing investment resources for research projects developed in Colombia during the term 2011 to 2012? (2013)
This essay is result of the documentary research about the impact of investment spending on the Colombian Institute of Anthropology and History budget during the years 2011 and 2012 . The reasons for writing about this issue are related to the influence of the execution of the investment in the public sector for cultural and economic development of a country and also the importance of compliance the ICANH mission to invest in order to investigate, generate and disseminate knowledge anthropological , archaeological, historical and cultural heritage of Colombia.